Reporting Guidelines for Music-based Interventions checklist: explanation and elaboration guide - Sheri L. Robb; K. Maya Story; Elizabeth Harman; Debra S. Burns; Joke Bradt; Emmeline Edwards; Tasha L. Golden; Christian Gold; Christian Gold; Christian Gold; John R. Iversen; Assal Habibi; et al. (Frontiers in Psychology)
BackgroundDetailed intervention reporting is essential to interpretation, replication, and eventual translation of Music-based Interventions (MBIs) into practice. Despite availability of Reporting Guidelines for Music-based Interventions (RG-MBI, published 2011), multiple reviews reveal sustained problems with reporting quality and consistency. To address this, we convened an interdisciplinary expert panel to update and improve the utility and validity of the existing guidelines using a rigorous Delphi approach. The resulting updated checklist includes 12-items across eight areas considered essential to ensure transparent reporting of MBIs.ObjectiveThe purpose of this explanation and elaboration document is to facilitate consistent understanding, use, and dissemination of the revised RG-MBI.MethodsMembers of the interdisciplinary expert panel collaborated to create the resulting guidance statement.ResultsThis guidance statement offers: (1) the scope and intended use of the RG-MBI, (2) an explanation for each checklist item, with examples from published studies, and (3) two published studies with annotations indicating where the authors reported each checklist item.ConclusionBroader uptake of the RG-MBIs by study authors, editors, and peer reviewers will lead to better reporting of MBI trials, and in turn facilitate greater replication of research, improve cross-study comparisons and meta-analyses, and increase implementation of findings.